Generalization of Gamma and Beta Functions with Certain Properties and Statistical Application - Rasheed, Maryam K.; Majeed, Abdulrahman H. (Iraqi Journal of Science, 2023)
This work is devoted to define new generalized gamma and beta functions involving the recently suggested seven-parameter Mittag-Leffler function, followed by a review of all related special cases. In addition, necessary investigations are affirmed for the new generalized beta function, including, Mellin transform, differential formulas, integral representations, and essential summation relations. Furthermore, crucial statistical application has been realized for the new generalized beta function.